Targeting miRNAs for drug discovery: a new paradigm - Nagpal, J K; Rani, R; Trink, B; Saini, K S (Current molecular medicine, 2010)
The discovery of miRNAs and the establishment of it's clinical links with multiple diseases has led to a paradigm shift in the drug development pipeline of major pharmaceutical companies and has given birth to several biotechnology enterprises revolving around these magic molecules. The miRNA profiling studies over the last few years have indicated implicit involvement of miRNAs in the pathobiology of cancer, diabetes, infectious diseases as well as cardiovascular, neurological and immune system disorders. This information is currently being translated into tools for diagnosis, prognosis and predicting response to treatment. In addition, active and vigorous investigations are ongoing in several laboratories across academia and industry to decipher the precise molecular functions and mechanism of action for key miRNAs with therapeutic potential. Knowledge gained from these efforts will surely pave the way for designing effective R&D strategies and will revolutionize the way we diagnose and treat various diseases. The present review attempts to track the evolutionary progression of microRNA research from it's early infancy years to its maturity into a dynamic field of drug discovery.